2022
DOI: 10.33734/diagnostico.v61i3.374
|View full text |Cite
|
Sign up to set email alerts
|

Estudio epidemiológico sobre el impacto de la pandemia COVID-19 en la salud mental de la población de Lima Metropolitana

Abstract: Objetivo: Identificar en la población adulta de la Lima Metropolitana la prevalencia, acceso y factores asociados a los principales trastornos mentales (TM) durante la pandemia COVID-19. Metodología: Estudio transversal, correlacional en una muestra probabilística, bietápica, de 1823 personas adultas (≥18 años), entrevistada vía telefónica. Instrumentos: Ficha sociodemográfica y características de vivienda; Cuestionario sobre Experiencias COVID-19; la MINI International Neuropsychiatric Interview Versión CIE-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…It should be noted that the COVID-19 pandemic could have affected the prevalence of psychiatric disorders as well. A population-based study in Peru showed an increase in the prevalence of anxiety and affective disorders after the COVID-19 lockdown, which could explain in part our findings regarding the increase of the number of psychiatric outpatient visits after May 2020 (33,34).…”
Section: Results In Contextmentioning
confidence: 60%
“…It should be noted that the COVID-19 pandemic could have affected the prevalence of psychiatric disorders as well. A population-based study in Peru showed an increase in the prevalence of anxiety and affective disorders after the COVID-19 lockdown, which could explain in part our findings regarding the increase of the number of psychiatric outpatient visits after May 2020 (33,34).…”
Section: Results In Contextmentioning
confidence: 60%
“…For convergent validity we used the Multicultural Quality of Life Index Scale (MLQI), translated and validated into Spanish even in the Peruvian context. 44,45 The MLQI is a one-dimensional instrument that measures the quality of life of people and is made up of 10 items, which evaluates physical well-being, psychological or emotional well-being, self-care and various levels of functioning in daily life that are condensed into a perception of overall quality of life. Each item is answered in a range from 1 to 10 (from bad to excellent).…”
Section: Instrumentsmentioning
confidence: 99%
“…Muchos casos de ansiedad y depresión no podían atenderse porque el sistema de salud pública en el país además de desarticulado y poco equipado, se hallaba desbordado. Los reportes de la OMS y de organizaciones de control de enfermedades en el mundo calculan que los casos de ansiedad y depresión aumentaron en un 26% y 28% en cifras prudentes (Saavedra et al, 2022). La prevalencia a 12 meses de trastornos mentales del 19,6%, los casos más frecuentes fueron de episodio depresivo con una prevalencia anual de 13,6% seguido por el trastorno de ansiedad generalizada (Saavedra et al, 2022).…”
Section: El Miedo O La Ansiedad Impulsan a Comportamientos De Riesgounclassified
“…Los reportes de la OMS y de organizaciones de control de enfermedades en el mundo calculan que los casos de ansiedad y depresión aumentaron en un 26% y 28% en cifras prudentes (Saavedra et al, 2022). La prevalencia a 12 meses de trastornos mentales del 19,6%, los casos más frecuentes fueron de episodio depresivo con una prevalencia anual de 13,6% seguido por el trastorno de ansiedad generalizada (Saavedra et al, 2022). En Perú, como en la mayoría de los países en desarrollo, no ha podido atenderse a todos los pacientes/afectados, como lo fue también en la mayoría de los países en desarrollo.…”
Section: El Miedo O La Ansiedad Impulsan a Comportamientos De Riesgounclassified
See 1 more Smart Citation